Selection of Optimal Candidates for Cytoreductive Nephrectomy in Patients with Metastatic Clear Cell Renal Cell Carcinoma: A Predictive Model Based on SEER Database - Zhang, Yishan; Hu, Jintao; Yang, Jingtian; Xie, Yingwei; Chen, Zhiliang; Shangguan, Wentai; Han, Jinli; He, Wang; Yang, Jingyin; Zheng, Zaosong; Zhong, Qiyu; Zhu, Dingjun; et al. (Frontiers in Oncology, 2022)
Background: Currently, the progress of targeted drugs in the treatment of metastatic clear cell renal cell carcinoma(mccRCC) is slow. Cytoreductive Nephrectomy (CN), as an alternative treatment, can improve the prognosis of patients with metastatic renal cell carcinoma to some extent. However, it is unclear which metastatic clear cell renal cell carcinoma patients would benefit from this tumor reduction operation. As a consequence, we developed a predictive model to identify patients who may well benefit from CN in terms of survival. Methods: We identified patients with metastatic clear cell Renal Cell Carcinoma retrospectively from the Surveillance, Epidemiology, and End Results (SEER) database (2010–2015) and classified them into surgery and non-surgery groups. Propensity score matching (PSM) was performed to balance the baseline characteristics. Patients who survived longer than the median overall survival (OS) of non-surgery group were defined as Surgical-benefit patients. Then, we developed a predictive model based on preoperative characteristics using multivariable Logistic regression. Calibration curves and the area under the receiver operating characteristic (AUC) were used to evaluate the predictive model's prediction efficiency. The clinical value of the nomogram was assessed utilizing decision curve analysis (DCA). Results: Our study collected 5544 patients from the SEER database, with 2352(42.4%) receiving cytoreductive surgery. Overall survival (OS) was longer in the CN group than in the non-surgery group after 1:1 Propensity Scoring Matching (median OS: 10.5 months vs 5 months; hazard ratio (HR) =0.4106, P< 0.001). In the matched Cytoreductive Nephrectomy group, there were 73.7% (412) patients survived more than 5 months after operation and they were viewed as the patients who could benefit from CN. The predictive model performed well on both training group (AUC=0.76) and validation group (AUC=0.81) and the Calibration curves indicated a high degree of consistency. The decision curve analysis curve demonstrated the clinical utility. We classified surgical patients into beneficial group and non-beneficial group by using the predictive model, then discovered a substantial difference in overall survival between the two groups. Conclusions: We developed a nomogram to select ideal mccRCC patients who might benefit from cytoreductive nephrectomy. Clinicians could make a more precise treatment strategy for mccRCC patients.